Towards a Comprehensive Dictionary of Gabonese French - Mavoungou, Paul A.; Ndinga-Koumba-Binza, Hugues Steve; Ompoussa, Virginie; Nyingone Assam, Blanche (Lexikos, 2022)
The present article reports on the conceptualization of the Dictionnaire Général du Français Gabonais. The dictionary project is a first of its kind in Gabonese lexicography. As an outcome of the inception of Gabonese French lexicography, the dictionary project arose from a discussion on the definition of Gabonese French, which Gabonese French lexicography should account for. In this article, the project background as well as the interests for the planned dictionary are presented. The article also deals with two key aspects of the dictionary conceptualization plan, i.e., lexicographic processes and the dictionary basis.Keywords: conceptualization plan, dictionary basis, dictionary project, French, Gabon, language appropriation, lexicographic processes